Steel Corp: Using Logistics Criteria to Segment Customers. Issue 1 (1st November 2018) - Manuj, Ila; Gerschberger, Markus; Freinberger, Patrick
Abstract : Steel Corp has a large production capacity but a shrinking steel market in Europe. Reaching growing markets like China and U.A.E will be important to sustaining and growing revenue but is tough due to higher transportation costs. In this case, users must identify and use logistics data; logistics customer segmentation and related cost analysis.